Chemical and textural interpretation of late-stage coffinite and brannerite from the Olympic Dam IOCG-Ag-U deposit. (1st December 2017) - Macmillan, Edeltraud; Cook, Nigel; Ehrig, Kathy; Pring, Allan
The Olympic Dam iron-oxide copper-gold-silver-uranium deposit, South Australia, contains three dominant U minerals: uraninite; coffinite; and brannerite. Microanalytical and petrographic observations provide evidence for an interpretation in which brannerite and coffinite essentially represent the products of U mineralizing events after initial deposit formation at 1.6 Ga. Marked compositional and textural differences between the various types of brannerite and coffinite highlight the role of multiple stages of U dissolution and reprecipitation. On the basis of petrography (size, habit, textures and mineral associations) and compositional variation, brannerites are divided into four distinct groups (brannerite-A, -B, -C and -D), and coffinite into three groups (coffinite-A, -B and -C). Brannerite-A ranges in composition from what is effectively uraniferous rutile to stoichiometric brannerite, and has elevated (Mg + Mn + Na + K) and (Fe + Al) compared to other brannerite types. It displays the most diverse range of morphologies, including complex irregular-shaped aggregates, replacement bands, and discrete elongate seams. The internal structure of brannerite-A consists of randomly-oriented hair-like needles and blades. Brannerite-B (<5 μm in size) is generally prismatic and typically associated with baryte and REY minerals (REE + Y = REY). Brannerite-C and -D are both associated with Cu-(Fe)-sulfides and are typically composed of irregular masses and blebs (10–50 μm in size) with a more uniform or massive internal structure. Brannerite-D is distinct from -C and always contains inclusions of galena. Brannerite-B to -D all contain elevated ∑REY, with brannerite-B and -C having elevated As, and brannerite-D having elevated Nb. All coffinite is typically globular (each globule is 2–10 μm in size) to collomorphic in appearance. Coffinite-A ranges from discrete globules to collomorphic bands completely encompassing quartz. Coffinite-B is always found with uraninite, and includes collomorph coffinite enveloped by massive uraninite, as well as aureoles of coffinite on the margins of uraninite crystals. Coffinite-C is associated with brannerite and REY minerals. The majority of coffinite is heterogeneous. Brannerite and coffinite have probably precipitated as part of a late-stage hydrothermal U-event, which might have involved the dissolution and/or reprecipitation of earlier precipitated uraninite, or could represent the products of a later U mineralizing event. Evidence which supports formation of late-stage coffinite and brannerite includes: (1) low-Pb contents of both minerals; (2) coffinite is commonly found on the edges of uraninite, implying later deposition; and (3) coffinite is often found on the edge of brannerite aggregates, suggestive of brannerite precipitation occurred before coffinite. Moreover, there are many features (e.g. banding, scalloped edges, alteration rinds, variable compositions etc.) indicative of hydrothermal alteration processes.